USE OF INFORMATION TECHNOLOGY IN TEACHING OPTICS IN SCHOOL PHYSICS COURSE - Janabergenova Gulnaz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article states about innovative technologies, non-traditional techniques, which can be used on the "Optics".